Prediction by a rapid enzymatic procedure of energy values and nitrogen digestibility of diets and feed ingredients for swine - Hsu, A; Allee, G.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A rapid in vitro method has been developed to predict digestibilities of nitrogen, dry matter (DM) and energy in feed ingredients and mixed diets for swine. A total of 21 samples, including nine feed ingredients and 12 mixed diets in which in vivo dry matter digestibility (DMD), nitrogen digestibility (ND), digestible engergy (DE) and metabolizable energy (ME) had been measured previously by conventional pig digestion trials were used in the in vitro assays. The in vitro procedure involved digestion of the sample with pepsin followed with amylase and pancreatin. The digestibilities of DM and protein were measured and compared to the values determined in vivo. A high correlation was found between the in vitro and in viva results for the digestibilities of DM, nitrogen and energy.
Keywords: Swine; Enzymes; Energy values; Nitrogen digestibility